2009
DOI: 10.1038/nature08711
|View full text |Cite
|
Sign up to set email alerts
|

Prejudice and truth about the effect of testosterone on human bargaining behaviour

Abstract: Both biosociological and psychological models, as well as animal research, suggest that testosterone has a key role in social interactions. Evidence from animal studies in rodents shows that testosterone causes aggressive behaviour towards conspecifics. Folk wisdom generalizes and adapts these findings to humans, suggesting that testosterone induces antisocial, egoistic, or even aggressive human behaviours. However, many researchers have questioned this folk hypothesis, arguing that testosterone is primarily i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
280
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 365 publications
(314 citation statements)
references
References 30 publications
26
280
1
2
Order By: Relevance
“…A previous administration study reported that beliefs about having received T or placebo were significantly correlated with proposer offers in the ultimatum game (Eisenegger et al, 2010). In our data, beliefs had no significant effect on rejection rates Evidence of a positive correlation between baseline T levels and low offer rejections was found in two previous studies (Burnham, 2007;Mehta and Beer, 2010).…”
Section: Beliefs and Baseline Tsupporting
confidence: 64%
See 3 more Smart Citations
“…A previous administration study reported that beliefs about having received T or placebo were significantly correlated with proposer offers in the ultimatum game (Eisenegger et al, 2010). In our data, beliefs had no significant effect on rejection rates Evidence of a positive correlation between baseline T levels and low offer rejections was found in two previous studies (Burnham, 2007;Mehta and Beer, 2010).…”
Section: Beliefs and Baseline Tsupporting
confidence: 64%
“…Secondly, subjects were aware of the fact that other participants were making offers after receiving T. Players' intentions and their degree of control over their actions are known to have important effects on fairness considerations and on subjects' responses to these actions (Falk et al, 2008). For this reason, folk wisdom about the effects of T on antisocial behavior (Eisenegger et al, 2010) may have easily affected responders' attitudes towards low ultimatum offers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a recent review by Bos et al (2013) showed that with the exception of one study with a relatively large sample size (Eisenegger et al, 2010; N = 121), previous T-administration studies have had an average of 18 participants, with a modal sample size of 16. Thus, the sample size and within-subject design in Experiment 1 made it a relatively powerful test of intra-individual variation in facial preferences.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%